Respostas

2014-05-22T18:40:37-03:00

a= -1                   y= -b+-( um em cima do outro) V (raiz   b² 4.a.c b=1                                           2.a

c=12                  

 y= -1 +- V 1² - 4.(-1).12                                           

   2.12                     

      y= -1 +-V 1 + 48                                       

 24                     

     y=-1 +- V 49                  

                  24                      

    y= -1+- 7                          

         24                        

  y'= -1 + 7  =   6 =  0.25

          24        24

y''= -1-7=     -8 = -0,33

        24       24